Dispersal of the Cotton Boll Weevil (Coleoptera: Curculionidae) in South America : Evidence of RAPD Analysis - Scataglini, María Amalia (2000)
RAPD technique provides useful information on the geographic origin and dispersal of the boll weevil Anthonomus grandis in South America. Nine populations from Argentina, Brazil, Paraguay, Mexico and USA were analyzed. Weevils were captured on native plants (Misiones province, Argentina) and on cotton cultures, except the sample from the United States (USDA laboratory-reared colony). A sample of the 'Peruvian square weevil', A. vestitus, from Ecuador, was included in the analysis in order to compare interspecific variation. The four primers used in the analysis revealed 41 'anonymous loci'. The neighbor-joining tree based on Nei's distances and values of Nm (migrants per generation), indicate that genetic similarity between samples from Tecoman (Mexico) and Puerto Iguazu (Argentina), is higher than among remaining South American populations. This result supports an hypothesis of natural occurrence of the boll weevil in South America, prior to extensive cotton cultivation. Population outbreaks of the species would be associated with increase of agricultural lands.